Supervisi Pendidikan Sebagai Ruang Belajar Bersama: Studi Kasus Sekolah Berbasis Kurikulum Merdeka di SMP Swasta Melati Binjai - Dewi, Nova Fitria; D, Hamidah; Damanik, Rabukit (SENTRI: Jurnal Riset Ilmiah, 2025)
This research is motivated by the importance of the principal's role as a supervisor in ensuring the successful implementation of the Merdeka Belajar Curriculum, which emphasizes independence, creativity, and innovation in the learning process. This study aims to describe in depth the principal's role as an academic supervisor in the implementation of the Merdeka Belajar Curriculum at Melati Binjai Private Junior High School. The study used a qualitative approach with field research and descriptive methods. Subjects included the principal, vice principals (curriculum, student affairs, and infrastructure), Islamic Education teachers, and several students. Data were collected through in-depth interviews, observations, questionnaires, and documentation studies. The results revealed several specific findings: (1) the principal implemented planned individual and group supervision, primarily through routine coaching, classroom observations, and checking learning administration; (2) the principal acted as a facilitator in encouraging teachers to understand the principles of the Merdeka Belajar Curriculum, particularly in the development of teaching modules and the implementation of differentiated learning; (3) open communication and a family-like work culture contributed to increased teacher professionalism and the effectiveness of curriculum implementation; (4) Supervision has an impact on increasing teacher readiness in designing innovative and relevant learning that meets student needs. Practically, this study shows that the successful implementation of the Independent Curriculum is highly dependent on the quality of consistent and collaborative supervision by the principal. However, this study is limited by its scope, which only covers one school, so the findings cannot be broadly generalized. Future research is recommended to involve more schools with different characteristics or examine digital supervision models to support the Independent Curriculum.